2017
DOI: 10.1002/syn.22020
|View full text |Cite
|
Sign up to set email alerts
|

THC alters alters morphology of neurons in medial prefrontal cortex, orbital prefrontal cortex, and nucleus accumbens and alters the ability of later experience to promote structural plasticity

Abstract: Psychoactive drugs have the ability to alter the morphology of neuronal dendrites and spines and to influence later experience-dependent structural plasticity. If rats are given repeated injections of psychomotor stimulants (amphetamine, cocaine, nicotine) prior to being placed in complex environments, the drug experience interferes with the ability of the environment to increase dendritic arborization and spine density. Repeated exposure to Delta 9-Tetrahydrocannabinol (THC) changes the morphology of dendrite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Chronic cocaine administration also increased spine density in the PFC, a brain area also targeted by DA neurons from the VTA (Robinson and Kolb 2004). Similar increases have also been described in response to nicotine (Brown and Kolb 2001), MDMA (Ball et al 2009), methamphetamine (Jedynak et al 2007) and THC (Kolb et al 2018). On the contrary, chronic alcohol (Zhou et al 2007) and morphine (Robinson and Kolb 1999), decrease the spine density in the NAc.…”
Section: Addiction and Da Structural Plasticitysupporting
confidence: 67%
“…Chronic cocaine administration also increased spine density in the PFC, a brain area also targeted by DA neurons from the VTA (Robinson and Kolb 2004). Similar increases have also been described in response to nicotine (Brown and Kolb 2001), MDMA (Ball et al 2009), methamphetamine (Jedynak et al 2007) and THC (Kolb et al 2018). On the contrary, chronic alcohol (Zhou et al 2007) and morphine (Robinson and Kolb 1999), decrease the spine density in the NAc.…”
Section: Addiction and Da Structural Plasticitysupporting
confidence: 67%
“…Considering all these pieces of evidence, we suggest that the changes that we have observed may emerge soon after the treatment and they would be long lasting. Indeed, it was previously reported that chronic exposure to THC modified the structure of the dendrites in the Nacc shell and the mPFC one month after THC cessation with lower doses than in the present study [ 34 ], and a more recent study reports that changes in spine density endures for 90 days in these regions [ 73 ].…”
Section: Discussionmentioning
confidence: 44%
“…Future research should also consider whether THC’s effects on neurons and microglia are related to addiction. Previous research indicates that chronic THC exposure in animals seems to activate microglia and produce neuroinflammation that may underlie some of the cognitive deficits associated with CUD (Melis et al 2017 ); additionally, changes in neuron and glia morphology after chronic cannabis exposure may also contribute to the persistent cognitive and behavioral deficits linked to CUD (Cutando et al 2013 ; Kolb et al 2018 ). Therefore, future studies should investigate whether chronic THC exposure in animals and humans is linked to changes in various cell types in the brain that contribute to cannabis addiction through neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%